American democracy promotion impulses, strategies, and impacts - Cox, Michael, 1947-; Ikenberry, G. John.; Inoguchi, Takashi (Oxford : Oxford University Press, 2000)
As we enter the 21st-century with American hegemony intact, this volume helps us understand what drives the world's last remaining superpower. It explores one of the least analysed, and most misunderstood aspects of American foreign policy.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Democracy -- United States; United States -- Foreign relations -- 1989-